A survey of the causes of sudden death in sport in the Republic of Ireland. Issue 4 (1st August 2000) - Quigley, Fionnuala
Abstract : Background —Sudden death in sport is rare, but when it occurs the effects are devastating. There have not been any reports to date describing the frequency and causes of sudden death in sport in the Republic of Ireland. Aim —To describe the incidence, possible causes, associated factors, and pathological findings in people who died while exercising in the Republic of Ireland in the 10 year period from January 1987 to December 1996. Methods —All 49 regional coroners in the Republic of Ireland were approached and details on all cases of sudden death in sport from 1 January 1987 to 31 December 1996 were requested. A questionnaire was used to document age, sex, participating sport, previous symptoms, previous medical investigations, circumstances of death, and main pathological finding in all reported cases. Results —Of the 49 coroners surveyed, 45 replied. A total of 51 cases of sudden death in sport were identified. The median age was 48 (range 15–78). Fifty of the deaths were of men. Golf was the most popular participating sport. In 42 cases, the pathological cause of death was atherosclerotic coronary artery disease. Conclusions —This is the first time the incidence of sudden death in sport in the Republic of Ireland has been described. The main cause of death in all age groups was atherosclerotic coronary artery disease.